Esophageal Achalasia: An Uncommon Complication during Pregnancy Treated Conservatively - Dimitrios Spiliopoulos; Michail Spiliopoulos; Alero Awala (Hindawi Limited, 2013)
A 38-year-old Caucasian woman, gravida 3 para 2, was admitted at 29 weeks of gestation because of vomiting, dysphagia for solids and liquids, and loss of weight. An enlargement of the anterior left neck region was noted on the palpation of the thyroid gland. An MRI of the neck showed a marked esophageal dilatation with the presence of food remnants along its length and the displacement of the trachea to the right. The findings of the upper gastrointestinal endoscopy and manometry were suggestive of esophageal achalasia. Conservative management with total parenteral nutrition (TPN) through a peripheral line proved to be successful. A healthy male baby was born by a cesarean section at 37 weeks. The patient underwent laparoscopic esophageal myotomy and fundoplication seven days postpartum.